Struktur Sosial Pelaksanaan Adat Hata Situtur Poda pada Pernikahan Masyarakat Angkola dan Mandailing - Naima Batubara; Abdullah Akhyar Nasution; Rakhmadsyah P. Rangkuty (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
This study aims to describe the social structure in the implementation of the Hata Situtur Poda custom in the marriage of the Angkola and Mandailing communities in Paringgonan Julu Village, Ulu Barumun District, Padang Lawas Regency, and identify the roles and responsibilities of each element in the social structure. The research method used is qualitative with a phenomenological approach. Data collection techniques include participant observation, in-depth interviews and study of related documents. Data analysis was done thematically by categorizing, describing, and drawing conclusions based on data obtained in the field. The results showed that the social structure of the implementation of Hata Situtur Poda involved various elements, namely the bride and groom, the parents of the bride and groom, the extended family of the bride and groom (kahanggi, anak boru, mora), traditional leaders (hatobangon, raja adat), religious scholars, government elements, and the wider community. Each element has specific and complementary roles and responsibilities in supporting the smooth running of the traditional procession. This tradition not only functions as a medium for conveying advice and advice on family life, but also as a mechanism for preserving cultural, moral and social values that have been passed down from generation to generation. This study concludes that the successful implementation of Hata Situtur Poda is highly dependent on a strong and organized social structure, which is able to maintain the continuity of the tradition amid the dynamics of changing times.